The Homophilic Domain – An Immunological Archetype - Kohler, Heinz; Bayry, Jagadeesh; Kaveri, Srinivas V. (Frontiers in Immunology, 2016)
The homophilic potential emerges as an important biological principle to boost the potency of immunoglobulins. Since homophilic antibodies in human and mouse sera exist prior environmental exposure they are part of the natural antibody repertoire. Nevertheless, hemophilic properties are also identified in induced antibody repertoire. The use of homophilicity of antibodies in the adaptive immunity signifies an archetypic antibody structure. The unique feature of homophilicity in the antibody repertoire also highlights an important mechanism to boost the antibody potency to protect against infection and atherosclerosis as well to treat cancer patients.